Specialized public order units: integrating a community policing mindset - Bürger, Bernd (Public Order Policing, 2024)
This chapter shows how the Unterstützungskommandos (USK), full-time public order units specializing in evidence gathering and arrests during assemblies, have evolved over recent decades. The events that triggered and accompanied these developments are described. The chapter also explains how community-focused policing became an organizational goal, and how it served as the foundation for operational tactics, as well as personnel selection, development, and training.